Penerapan Model Pembelajaran Kooperatif Tipe Numbered Heads Together Berbantuan Media Interaktif untuk Meningkatkan Aktivitas dan Prestasi Belajar Siswa - Agni Era Hapsari (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2017)
This study aimed to improve history learning achievement through the implementation of cooperative learning model NHT assisted interactive media. The method used in this research was a classroom action research by conducting two meetings in two cycles. The instrument used was questionnaire for the interview and questionnaire for observation of learning activities and achievement test. Data analysis techniques used was comparative descriptive method by comparing pre cycle and between cycles. The results of the study in the first cycle was the activity of 12 students or 40% in the high category, activity 9 students or 30% was in medium category and the activity of another 9 students or 30% was in lower categories. It was found that 24 students or 70% were mastery learning with average grade 62.25. In the second cycle, the activity of 24 students or 80% was in higher category, activity of 6 students or 20% was in medium category, and 0 student or 0% in lower categories. The average of learning achievement reached 85 with 30 students mastery learning or 100%. Based on the analysis and discussion of the research, it is concluded that the implementation of cooperative learning model NHT aided interactive media can improve student achievement.